Biomarcadores fisiológicos para detecção de efeitos residuais de picloram no solo - Carrara, Bruna Helena (2021)
Weed control in pastures is essential to improve productivity in agriculture and the correct and conscious use of herbicides is very important to reduce the problems caused by the residual effect on subsequent crops. Therefore, the objective of this study was to detect the residual effects of the herbicide picloram in the soil through a physiological biomarker of the soybean plant. The study was carried out in a greenhouse in a randomized block design, in a 6 × 2 factorial scheme, with the factors consisting of six concentrations of the herbicide picloram (0; 0.125; 0.25; 0.50; 1.00; 2 .00 μg kg-1) and two soybean varieties (AN 84 024RR and AN 88 022SC) and four replications. The herbicide picloram was applied to the soil seven days before planting, simulating residual concentrations with surface applications with a spray volume equivalent to 200 mL vase-1 using a manual sprayer. Twenty days after sowing, where the plants had the first fully expanded trifoliate, the photochemical parameters and the enzymatic parameters Ptotal, APX, CAT, POD, MDA, plant height were evaluated and phytotoxicity was determined. The herbicide induces distinct metabolic responses in soybean plants, promoting changes in plant metabolism. The determination of photochemical parameters plant height and determined the phytotoxicity. The herbicide induces distinct metabolic responses in soybean plants, promoting changes in plant metabolism. The determination of photochemical parameters plant height and determined the phytotoxicity. The herbicide induces distinct metabolic responses in soybean plants, promoting changes in plant metabolism. The determination of photochemical parameters ɸFIIe, ETR and Rfd show promise as physiological biomarkers in soybean plants to detect picloram residues in soil at low concentrations.